DETEKSI LEMAK BABI SEBAGAI ADULTERAN DAGING SAPI, AYAM DAN KAMBING MENGGUNAKAN FOURIER TRANSFORM INFRARED SPECTROSCOPY DERIVATIVE - Ul Husna Az Zaera, Asma
Indonesia is a country which has Islam as its major religion. The present of lard in foods is serious problem in views of several religious concerns because some religions like Islam forbid their followers to consume any foods containing porcine and its derivatives. FTIR spectroscopy has been developed to simple analysis of difference between lard with body fat of cow, chicken, and lamb. The infra-red spectral bands from lard, body fat of cow, body fat of chicken, and body fat of lamb were scanned, interpreted, and identified to qualitative differentiate. Ratio between spectral peak of second derivative of absorbance at wavelength 1079 and 1130 cm -1 tested statistically using independent ttest wit p value=0,05 and Levene’s test as differentiating analysis. The result of independent t-test were the average of lard 0,6908 ±0,0375, and for body fat of cow 0,6991 ±0,0148, body fat of lamb 0.6964 ±0.02, and body fat of chicken 0,6931 ±0.0404. The result of Levene’s test were Sig. value of lard, body fat of cow, body fat of chicken, and body fat of chicken is as follows 0,012, 0,017, dan 0,002. Based on statistic result, the conclusion is there are significance difference between lard and body fat of cow, lard with body fat of chicken, and lard with body fat of lamb.